Website development for electromagnetic theory (e-learning) / Ekmal Hisham Alias - Alias, Ekmal Hisham (2006)
This thesis presents the development of an e-learning website for one of the degree courses taught in Universiti Teknologi MARA. The course is Electromagnetic Theory. Since this course is very abstract, the website is hoped to aid the teaching and learning process. Electromagnetic Theory is the study of the electric fields and magnetic fields, around us. Students need to visualize such fields in order to understand the course. If these fields could be displayed through the use of programming software, the teaching and learning process could be further enhanced. This website is designed to be interactive and user friendly where the user is able to interact and used the website easily. This website contains lecturer's note, tutorials and past year examination question papers obtained from reliable resources such as text books, lecturer's note and other universities website. This website also include interactive program where the user can interact and answer to the given set of questions and also perform mathematical calculation. The user needs to log-in to the website in order to use all the privilege offered. This project is created and built using PHP: Hypertext Preprocessor as the scripting language. The server used is Apache and MySQL is used for its database.